2012
DOI: 10.1007/s10384-012-0186-8
|View full text |Cite
|
Sign up to set email alerts
|

Three-month evaluation of dorzolamide hydrochloride/timolol maleate fixed-combination eye drops versus the separate use of both drugs

Abstract: The replacement of concomitant treatment with dorzolamide hydrochloride 1 % and timolol maleate 0.5 % eye drops with dorzolamide hydrochloride 1 %/timolol maleate 0.5 % fixed-combination eye drops improved protocol adherence and preserved the IOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
3
14
0
Order By: Relevance
“…The LTFC eye drops had varying effects on IOP [27], but IOP did not change after switching to DTFC eye drops [8–11]. Our results are in agreement with these observations.…”
Section: Discussionsupporting
confidence: 89%
“…The LTFC eye drops had varying effects on IOP [27], but IOP did not change after switching to DTFC eye drops [8–11]. Our results are in agreement with these observations.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to the current study, which demonstrated comparable efficacy of BRINZ/TIM-FC and unfixed concomitant BRINZ + TIM, other clinical assessments of fixed-combination therapies have demonstrated that fixed-combination pharmacotherapies containing TIM and dorzolamide, a carbonic anhydrase inhibitor, or latanoprost, a prostaglandin analog, have efficacy similar to that of concomitant treatment with their active components 3235. Fixed-combination dorzolamide 1%/TIM is approved for use in Japan; there are currently no comparative data for BRINZ/TIM-FC versus the fixed combination of dorzolamide 1%/TIM.…”
Section: Discussionsupporting
confidence: 80%
“…Patients were eligible if they were receiving treatment with multiple IOP-lowering drugs (including combination drugs) at screening, or if they were treated with a single IOP-lowering drug and had insufficient IOP reduction at screening. Insufficient IOP reduction was defined as IOP >18 mmHg in at least one eye at the screening visit (primary open-angle, exfoliation, or pigmentary glaucoma)28,29 or IOP elevation <30% from the screening visit to the baseline visit (normal-tension glaucoma). In previous studies, reducing IOP to <18 mmHg in patients with open-angle glaucoma or by ≥30% in patients with normal-tension glaucoma resulted in slower rates of visual field progression 9,30,31.…”
Section: Methodsmentioning
confidence: 99%